The Effect Of Hotel And Restaurant Tax On Kabupaten Bantul’s Local Revenue In 2016-2024 - Sriniyati; Alda Tri Yuliani (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
The purpose of this study was to examine the effects of hotel tax and restaurant tax towards Kabupaten Bantul’s local revenue (PAD). Data used in this research was time series data from 2016 until 2024. Data used in this research was secondary data collected from Kabupaten Bantul’s official website. To test the hypotheses, this study used hypotheses testing through the Warp PLS 8.0. The results of this study gave empirical evidence that hotel tax had a positive and significant effect on Kabupaten Bantul’s local revenue (PAD).